Recitation of Surah al-Insyirah and al-Qadr in the Bayen Tradition Based on Peter L Berger Sociology of Knowledge Perspective - Annisa Fadlilah (Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
This study discussed the response of the Wonokerto community to the Quran, dealing with the recitation of Surah al-Insyirah and al-Qadr in the Bayen tradition. This research, which belongs to the Living Quran area, is interesting because the use of both surahs on Bayan tradition is rare. The principal issues that will be answered in research is how the implementation of Bayen tradition as well as transmission and transformation practice of reciting surah al-Insyirah and al-Qadr in Bayen tradition using Peter L. Berger Sociology of knowledge theory. The dialectical triad in Peter L Berger's sociology of knowledge consists of externalization, objectivity and internalization produced the following research conclusions: The transmission of reciting surah al-Insyirah and al-Qadr in the Bayen tradition originated from the process of externalizing the knowledge of the kiai (Islamic leaders) namely KH Dahlan, KH Zaenuri and Kiai Nurul Huda about the practice of the tarekat obtained through ijazahs and then passed on to the general public. People who tend to obey their teachings accept the practice and implement it together so that the practice experiences an objectivity process into an agreed tradition. Society as the perpetrators of tradition has their own internalization which is subjective about the meaning and motivation of doing the deeds, including for protection from negative things, as a non-material strength for pregnant women, as a deterrent to lust, and so forth. While the transformation of this practice occurred because of differences in externalization experienced by Kiai Dahlan and Kiai Nurul Huda who were met with different conditions in society. This practice of deformation took the form of omitting the recitation of manaqib and was only replaced by reciting surah al-Insyirah and al-Qadr which were previously surahs recited as etiquette before reciting the manakib